The AYO SELAMATKAN LINGKUNGAN MELALUI PENGELOLAAN SAMPAH PLASTIK DENGAN MEMBUAT PRODUK ECOBRICK: LET'S SAVE THE ENVIRONMENT THROUGH PLASTIC WASTE MANAGEMENT BY MAKING ECOBRICK PRODUCTS - Hendra Poltak; Asmira Rumalolas; Renaldo Fredly Rumaherang; Muh Guntur Ketuut; Nur Anjelika Saputri; Zakeus Wuarbanaran; Ristiana Dwi Cahyani; Simon Manutilaa; Leoni Hayu Sabrina Putri; Handayan Handayani; Muhfizar Muhfizar; Muh Kasim; Yani Nurita Purnawanti; Asthervina Widyastami Puspitasari (Politeknik Kelautan dan Perikanan Sorong, 2023)
Plastic waste management is an important issue in efforts to maintain environmental sustainability. Efforts to control plastic waste are carried out through training on making ecobricks as a management of plastic waste to student partners at MI Al Ikhtiar Al Ma'arif 4 School, Sorong Regency on December 9, 2022. This training aims to increase awareness the public about the importance of managing plastic waste and to introduce the ecobrick concept as a solution in plastic waste management. The method of implementing the training is through hands-on practice of making ecobricks and delivering material on the introduction of waste and the environment and the role of ecobricks in overcoming the problem of plastic waste. The results of the training through showed an increase in participants' understanding and skills in managing plastic waste using ecobricks.